Penafsiran Tentang Pendidikan Birr al-Walidayn dalam Surat Al-Isra’ Ayat 23-24 - Komaru Zaman; Rofi’atul Afifah; Rizki Dwi Oktavia (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Birr al walidayn education is one of the most important factors in ideal character education. The creation of a generation that has good character is a dream for parents to their children. Birr al walidayn education is very influential on adab to parents. In the Qur'an, Allah SWT. has explained many verses related to Birr al walidayn. Allah tells the story of a mother's struggle so that a child can know the struggle of a mother so that she can repay him by being kind to him and not being disobedient to him, even if one of them is not to say